Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/anie.201306783
|View full text |Cite
|
Sign up to set email alerts
|

Methylaluminum‐Supported Rare‐Earth‐Metal Dihydrides

Abstract: Compounds combining the large rare-earth-metal (Ln) centers with the smallest anionic ligand, H À (hydrido), continue to pose challenging questions both in fundamental and applied chemistry. [1] The inherent bonding properties in solid-state binary LnH x phases (e.g., causing metallic behavior) as well as in ligand-supported molecular counterparts (revealing unique cluster chemistry, see Supporting Information) have been the focus of extensive research. Moreover, heterobimetallic solid-state materials, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 52 publications
1
36
0
1
Order By: Relevance
“…X‐ray diffraction studies revealed the expected molecular structure (see Figure S1). The Y–N(imide) bond lengths in 2 average 2.126 Å (three independent molecules in the unit cell) and lie well within the expected range compared to previously reported LA‐supported yttrium imide complexes 12b,12c,18. As for the previously synthesized B ′‐type imide complexes,12b,12c compound 2 could not be converted into a terminal imide complex, neither thermally nor by addition of neutral Lewis bases like 1,4‐dioxane, pyridine, tmeda ( N , N , N′ , N′ ‐tetramethylethylenediamine), or DMAP.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…X‐ray diffraction studies revealed the expected molecular structure (see Figure S1). The Y–N(imide) bond lengths in 2 average 2.126 Å (three independent molecules in the unit cell) and lie well within the expected range compared to previously reported LA‐supported yttrium imide complexes 12b,12c,18. As for the previously synthesized B ′‐type imide complexes,12b,12c compound 2 could not be converted into a terminal imide complex, neither thermally nor by addition of neutral Lewis bases like 1,4‐dioxane, pyridine, tmeda ( N , N , N′ , N′ ‐tetramethylethylenediamine), or DMAP.…”
Section: Resultssupporting
confidence: 85%
“…We applied the superbulky monoanionic Tp t Bu,Me {hydrotris(3‐ tert ‐butyl‐5‐methylpyrazolyl)borate} ligand to enter [Ln=X](LA)‐type chemistry of the larger rare‐earth metals. Representative monolanthanide examples of the type A′ and B′ include [(Tp t Bu,Me )La(=CH 2 )(AlMe 3 ) 2 ]11b and [(Tp t Bu,Me )Ln(=NAr)(AlHMe 2 )] (Ar = C 6 H 3 Me 2 ‐2,6) 12b. Spurred by the rich chemistry exhibited by Chen's scandium terminal imide complexes,9,17 we focused our efforts on the synthesis of the corresponding B ‐type imide complexes (of the larger rare‐earth elements).…”
Section: Introductionmentioning
confidence: 99%
“…The super-bulky hydrotris[3-tert-butyl-5-methylpyrazolyl] borate ligand Tp tBu,Me allowed the isolation of the heterometallic complexes (Tp tBu,Me )Ln[(-H)AlMe 3 ] 2 (Ln = Y, Lu), which could be transformed into the imido complexes (Tp tBu,Me )Ln[(-NC 6 H 3 Me 2 -2,6)(-H)AlMe 2 ] by subsequent reaction with 2,6-dimethylaniline according to Scheme 123 [108].…”
Section: Heterobimetallic Organolanthanide Complexesmentioning
confidence: 99%
“…9 Furthermore, complexes of the type Cp R Ln(AlMe 4 ) 2 were successfully applied in C-H bond activation protocols giving access to the first structurally characterized rare-earth metal methylidyne 10 and methylidene complexes. 13 One major finding was that the superbulky monanionic Tp tBu,Me (= hydrotris(3-tert-butyl-5-methyl-pyrazolyl)borate) ligand can afford monolanthanide derivatives of the type [(Tp tBu,Me )-Ln(NAr)(AlHMe 2 )] (Ar = C 6 H 3 Me 2 -2, 6) 14 and [(Tp tBu,Me )Ln(NR)-(AlMe 3 )] (Ln = Y, Ho; R = tBu, adamantyl). 13 One major finding was that the superbulky monanionic Tp tBu,Me (= hydrotris(3-tert-butyl-5-methyl-pyrazolyl)borate) ligand can afford monolanthanide derivatives of the type [(Tp tBu,Me )-Ln(NAr)(AlHMe 2 )] (Ar = C 6 H 3 Me 2 -2, 6) 14 and [(Tp tBu,Me )Ln(NR)-(AlMe 3 )] (Ln = Y, Ho; R = tBu, adamantyl).…”
Section: Introductionmentioning
confidence: 99%